(untitled) (Journal of Parents and Teachers, 2017)
During the 1930s, a young Jewish man named Bobby Dorfman abandoned his family’s home and work security in New York City to prove his fortune by working for his uncle Phil Stern, based in Los Angeles as a producer and agent of some of the most important Hollywood stars. Phil instructs his secretary Vonnie to show Bobby the city and explain the ins and outs of the American film industry that, despite its glamor, displeases the girl because of her frivolity. In time, they both find a solid friendship that is put into question when Bobby assumes his love for Vonnie, who in turn secretly maintains a romance with Phil, married and unable to leave his wife. A love triangle that through encounters and disagreements will force Bobby, and also Vonnie, to mature his vision about love, the importance of the passage of time, and sometimes the unfair irrationality of passion